DAMPAK MODEL MEMBACA TERPANDU BERBASIS GENAI-SYNTHESIA TERHADAP KEMAMPUAN MEMBACA, MOTIVASI MEMBACA, DAN PERSEPSI SISWA - Hera Wahdah Humaira; Iin Khairunnisa (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
Thisstudy investigated the impact of a GenAI-synthesia-based guided reading model and cultural content on students' reading ability, motivation, and perspectives. The research method used in this study was a quasi-experiment involving 200 high school students. The instruments used included textual and inferential reading assessments, a reading motivation assessment scale, texts containing local cultural content, and GenAI-Synthesia. This study also collected qualitative data through interviews with several participants. Data analysis used descriptive statistics, independent-samples t-tests, chi-square tests, and qualitative analysis of interview results. The research findings indicate that the GenAI-synthesia-based guided reading model can improve reading ability, motivation, and positive perspectives. The integration of cognitive and practical activities in supporting reading skills contributes significantly to reading competence. Positive perspectives on the intervention were evident in its role in enriching cultural knowledge, encouraging the sharing of understanding and experiences, and improving life skills in the community. This study suggests that integrating technology with texts containing local cultural content can significantly improve reading ability.